2015
DOI: 10.1002/chem.201500887
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Ionic‐Liquid Gels with High Ionic Conductivity

Abstract: Supramolecular ionogels were prepared by the gelation of room-temperature ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate ([BMIm][BF4 ]) with (S,S)-bis(leucinol)oxalamide. Remarkably, the ionic conductivity of solutions and ionogels with low gelator concentrations is higher than that of neat [BMIm][BF4 ]. On the basis of molecular dynamics simulations and quantum mechanical calculations, the origin of this phenomenon is attributed to the higher affinity of gelator molecules towards [BF4 ](-) ions, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…GC-MS analyses were run with a Shimadzu QP50 using a Rtx-5MS column (30 m × 0.25 mm × 0.10 µm); injector temperature of 260 °C; He as carrier (1 mL min ) were added to a Fischer-Porter reactor containing the appropriate amount of catalyst (0.1 µmol Pd). After that, the reactor was pressurized with H 2 (2, 3, 4, 5, 6 or 8 bar) and heated (20,40,60,80 or 100 °C). Samples were taken from the reaction mixture and the conversion and selectivity were determined by GC analysis of the reaction samples.…”
Section: Mechanistic and Kinetic Studiesmentioning
confidence: 99%
“…GC-MS analyses were run with a Shimadzu QP50 using a Rtx-5MS column (30 m × 0.25 mm × 0.10 µm); injector temperature of 260 °C; He as carrier (1 mL min ) were added to a Fischer-Porter reactor containing the appropriate amount of catalyst (0.1 µmol Pd). After that, the reactor was pressurized with H 2 (2, 3, 4, 5, 6 or 8 bar) and heated (20,40,60,80 or 100 °C). Samples were taken from the reaction mixture and the conversion and selectivity were determined by GC analysis of the reaction samples.…”
Section: Mechanistic and Kinetic Studiesmentioning
confidence: 99%
“…Previous reports demonstrated that the conductivity of ionogels is at best equal to or slightly higher than that of neat IL. Aleksandra and coworkers have also reported slightly higher ionic conductivity of supramolecular ionogel than that of neat ionic liquid 1-butyl 3-methyl imidazolium tetrafluoroborate [48]. High ionic conductivity of PEDOT: PSS/IL films as compared with that of pure PEDOT: PSS and IL have been published by Liu et al Origin of this higher value of conductivity was attributed to interactions between poly ionic PEDOT; PSS and IL.…”
Section:  (2)mentioning
confidence: 80%
“…In this way all of the reported computational data correspond to the gas-phase Gibbs free energies at a temperature of 298.15 K and a pressure of 1 atm. The choice of such a computational setup was prompted by our recent success in modeling the properties of gelator molecules [23] and metal binding affinities [24], as well as correctly reproducing thermodynamic and kinetic parameters of organic [25,26] and enzymatic [27] reactions. In order to circumvent problems with the flexibility of the investigated systems, we tried many different conformations in each studied case and report here the results corresponding to the most stable structures.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The ability of oxalamide derivatives (1-4) to form supramolecular gels by means of extended hydrogen bonded chains has given rise to a rich field of synthetically and externally tunable soft materials, which has been the subject of intense investigation in recent years [5][6][7][8][9]23]. Addition of hydrochloric acid, various metal salts, or ions to the gels significantly affects their gelation properties.…”
Section: Disruption Of Gelsmentioning
confidence: 99%